Verteporfin inhibits the cGAS-STING pathway and improves the tumor microenvironment during cisplatin treatment in hepatocellular carcinoma - Gong, Yi; Xiong, Yajun; Gao, Yuting; Song, Xiaoyong; Gong, Yanli; Wang, Dan; Liu, Zhihan; Yang, Yanguang; Lu, Junlan; Zou, Isabelle Xinyue; Shi, Xinli (Frontiers in Immunology, 2025)
BackgroundCisplatin (DDP) is a clinical first-line chemotherapy drug for hepatocellular carcinoma (HCC), but treatment is often ineffective due to drug resistance. Yes-associated protein 1 (YAP1) is a critical regulator/factor in HCC tumor progression. Our previous research showed that DDP promoted the expression of YAP1 in mice bearing H22 cell in situ liver tumors, which might be related to the poor therapeutic effect of DDP.Methods and resultsDDP could inhibit tumor growth and decrease tumor volume in DEN/TCPOBOP-induced HCC mice, increase the number of CD8+ T cells in the tumor, reduce the proportion of PD-1+CD8+ T cells in the peripheral blood and spleen of mice, and reduce the immune exhaustion of the tumor microenvironment in HCC. Of note, that DDP treatment activated YAP1 expression in HCC cells. In addition, using a murine model of subcutaneous transplantation of HCC cells, it was found that the combined use of the YAP1 inhibitor, verteporfin, and DDP led to significant tumor regression. Inhibition of YAP1 reduced activation of the cGAS-STING pathway by DDP treatment. Furthermore, bioinformatics analysis revealed that YAP1 was positively correlated with cGAS and STING in HCC tissues. We further confirmed the correlation of YAP1 with cGAS-STING in HCC using two models: DEN/TCPOBOP induction of HCC in hepatocyte-specific Yap1 knockout mice; and giving verteporfin treatment to mice with subcutaneously transplanted HCC tumors. Inhibiting the expression of YAP1 in HCC tissues can reduce the expression of cGAS-STING and enhance the therapeutic effect of cisplatin.ConclusionsThe combination of YAP1 inhibitor, verteporfin and DDP enhances anti-tumor immunity by regulating the interaction between YAP1 and cGAS-STING in the tumor microenvironment, providing new insights into a combined chemotherapy strategy for HCC.